Implementation of the Ethnoscience-Based Contextual Teaching and Learning (CTL) Model in Science Learning for Class V of Al-Munawwarah Elementary School, Jambi City - Hana Thahirah; Mahluddin Mahluddin; Kiki Fatmawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model based on ethnoscience in science-social (IPAS) learning for fifth-grade students at Madrasah Ibtidaiyah Al-Munawwarah, Jambi City. This research employed a qualitative approach with a case study design. Data were collected through classroom observation, in-depth interviews with teachers and students, and documentation. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings indicate that the implementation of CTL based on ethnoscience creates contextual learning, enhances students’ active participation, and helps students connect IPAS concepts with cultural and environmental phenomena around them. The integration of local values and real-life experiences strengthens conceptual understanding and fosters reflective scientific attitudes. Therefore, the CTL model based on ethnoscience is effective as a learning approach in Islamic elementary schools.